Circular RNA circ_0076631 promotes coxsackievirus B3 infection through modulating viral translation by sponging miR-214-3p - Qin, Ying; Lin, Lexun; Yang, Shulong; Dai, Zongmao; Zhang, Congcong; Huang, Jingjing; Deng, Fengzhen; Yue, Xinxin; Ren, Long; Fei, Yanru; Zhao, Wenran; Wang, Yan; et al. (Frontiers in Microbiology, 2022)
Coxsackievirus B (CVB), a member of Enterovirus genus of Picornaviridae, is the leading pathogens of viral myocarditis and dilated cardiomyopathy. The pathogenesis of CVB induced myocarditis has not been completely elucidated, and no specific antiviral measurement is available presently. Circular RNAs (circRNAs) have been reported to be able to modulate viral replication and infection through bridging over noncoding RNAs (ncRNAs) and coding messenger RNAs (mRNAs). To date, the role of circRNAs in CVB infection is largely unknown. In this study, we found that hsa_circ_0076631 (circ_0076631) significantly promoted CVB type 3 (CVB3) replication. Further study showed that the underneath mechanism was circ_0076631 indirectly interacting with CVB3 through sponging miR-214-3p, which targeted the 3D-coding region of CVB3 genome to suppress viral translation. Knocking down circ-0076631 caused a suppression of CVB3 infection, thus, circ-0076631 may be potential target for anti-CVB therapy.